Rural leisure opportunities for people with disabilities: needs and challenges in Quebec. Issue 1 (2nd January 2019) - Roult, Romain; Carbonneau, Hélène; Belley-Ranger, Émilie; Brunet, Isabelle; Adjizian, Jean-Marc
ABSTRACT: The issue of leisure for people with disabilities is central as the practice of these activities helps counteract certain problems of sedentariness, social isolation or stigmatization. This problematic is even more complicated in rural areas, where limited means, as well as geographical location and scope slow down certain avenues of leisure development for these challenged populations. The objective of this study was to seek to understand the realities experienced by partners of the Quebec Association for Leisure of People with Disabilities. Through focus groups and semi-directed interviews conducted with 70 local actors, this study highlights the fact that these challenged populations can enjoy a fair amount of leisure time, although it is increasingly difficult to maintain due, in particular, to precarious financial and human situations. The analyses also suggest that future challenges regarding this issue will be linked to partnerships, planning and programming considerations.